Lack of parthenogenesis by Amblyomma cajennense (Acari: Ixodidae) - Carolina MV de Freitas; Romário C Leite; Cristina ML Lopes; Daniel S Rodrigues; Gustavo Fontes Paz; Paulo R de Oliveira (Memorias do Instituto Oswaldo Cruz, 2002)
Some reproductive parameters of adult stages of Amblyomma cajennense ticks were studied. The capacity of virgin females to reproduce by parthenogenesis was evaluated, during an experimental infestation, in absence of males, on a horse (Equus cabalus). Ticks were spread either completely free or in limited sites on the body of the animal. The engorged virgin females showed longer feeding periods and lighter body weights than those that had been fertilized. Some of these unmated females produced smaller egg masses, which had no embryonary development. On the other hand, females that had been inseminated produced larger egg masses, with normal embryonary development that led to viable larvae. Under the studied conditions, A. cajennense females did not reproduce by parthenogenesis.